EFFECTIVENESS OF KONI TUBAN MONITORING SYSTEM APPLICATION IN SPORTS WEEK PREPARATION IN EAST JAVA PROVINCE - Dwinanda Saputra, Ahmad Faris; Pramono, Harry; Rumini, Rumini (Journal of Physical Education and Sports, 2020)
This study aims to develop a KONI monitoring system in Tuban District and to find out the effectiveness of an android-based monitoring system application for the preparation of Sports Week in East Java Province. This research uses the procedural method of the Borg and Gall development model using only three steps, namely, research and data collection, planning, and development. The research subjects of KONI administrators in Tuban or the Special Team for the Preparation of Provincial Sports Week are named SATLAK PANTAS (Implementing the Program for Adding Gold Programs), administrators of sport branches, and athletes. The results of this study are android-based application products, which are named E-Monitoring Athlete Success Tuban or abbreviated as E-MAS Tuban, and respondents' responses from the aspect of application effectiveness get a percentage rating of 93%. From the aspect of the application, functions get a percentage rating of 93%. Based on the results of this study, the conclusions obtained are the effectiveness and function of the KONI monitoring system application in Tuban as a good medium for monitoring sports branches in preparation for the Sports Week in East Java Province.